Desorption ionization using through‐hole alumina membrane offers higher reproducibility than 2, 5‐dihydroxybenzoic acid, a widely used matrix in Fourier transform ion cyclotron resonance mass spectrometry imaging analysis. (29th March 2021) - Hasan, Md. Mahmudul; Eto, Fumihiro; Mamun, Md. Al; Sato, Shumpei; Islam, Ariful; Waliullah, A.S.M.; Chi, Do Huu; Takahashi, Yutaka; Kahyo, Tomoaki; Naito, Yasuhide; Kotani, Masahiro; Ohmura, Takayuki; et al.
Abstract : Rationale: DIUTHAME (desorption ionization using through‐hole alumina membrane), a recently developed matrix‐free ionization‐assisting substrate, was examined for reproducibility in terms of mass accuracy and intensity using standard lipid and mouse brain sections. The impregnation property of DIUTHAME significantly improved the reproducibility of mass accuracy and intensity compared with 2, 5‐dihydroxybenzoic acid (DHB). Methods: Frozen tissue sections were mounted on indium tin oxide‐coated glass slides. DIUTHAME and DHB were applied to individual sections. Subsequently, a solution of a phosphatidylcholine standard, PC(18:2/18:2), was poured onto the DIUTHAME and matrix. Finally, the samples were subjected to laser desorption ionization coupled with Fourier transform ion cyclotron resonance mass spectrometry. The reproducibility was tested by calculating the mean ± standard deviation values of mass errors and intensities of individual ion species. Results: Analysis of the PC(18:2/18:2) standard showed significantly ( p  < 0.01) lower mass error for DIUTHAME‐MS than for MALDI‐MS. Endogenous PC(36:4) analysis in mouse brain section also showed significantly ( p  < 0.05) lower mass errors for DIUTHAME‐MS. Furthermore, we investigated the mass error of some abundant lipid ions in brain sections and observed similar results. DIUTHAME‐MS displayed lower signal intensity in standard PC analysis. Interestingly, it offered higher signal intensities for all the endogenous lipid ions. Lower fluctuations of both mass accuracies and signal intensities were observed in DIUTHAME‐MS. Conclusions: Our results demonstrated that DIUTHAME‐MS offers higher reproducibility for mass accuracies and intensities than MALDI‐MS in both standard lipid and mouse brain tissue analyses. It can potentially be used instead of conventional MALDI‐MS and mass spectrometry imaging analyses to achieve highly reproducible data for mass accuracy and intensity.